Skin-toned tattoo ink: what should one expect in terms of ink darkening and removal when treated with a 755 nm pico-second laser? - Menozzi-Smarrito, Candice; Smarrito, Stéphane (Aesthetic Medicine, 2024)
Background: Picosecond lasers have demonstrated their efficiency in tattoo removal. However, the removal of micropigmentation remains challenging due to the complexity of cosmetic skin-toned inks that contain titanium and iron oxides. Aim : The current work aims at further investigating how the concentration of mineral oxides and the fluence can impact the color change and at assessing the darkening process and the removal efficiency when a skin-toned cosmetic tattoo was treated with a picosecond laser. Methods : Model ink samples as well as a skin-toned eyebrow tattoo were treated with a picosecond laserusing fluences from 0.21  to 5.25 J/cm2. Digital photographs were taken and color contrast was analyzed with ImageJ software. Analyses of variance were performed with Excel software. Results : At a fluence threshold, the greyish discoloration of TiO2 model inks occurred, then the color contrast increased with the fluence until reaching a plateau. Interestingly, a synergetic effect between iron and titanium oxides might occur. Darkening was also observed in vivo during the treatment of an eyebrow tattoo containing flesh inks. The tattoo became first greenish, then darker and finally the pigmentation started decreasing after the 8th session. 11 treatments were necessary to completely remove the tattoo. Conclusion : The 755 nm picosecond laser has demonstrated its efficiency to remove complex tattoo containing flesh pigments. The ink darkening seems to be inevitable during the treatment, however, it should not be seen as a complication but as a part of the elimination process.